Functional encryption - Ahmad, Khairol Amali Bin; Ahmad, Khaleel; Dulhare, Uma N. (Switzerland Springer, 2021)
This book provides awareness of methods used for functional encryption in the academic and professional communities. The book covers functional encryption algorithms and its modern applications in developing secure systems via entity authentication, message authentication, software security, cyber security, hardware security, Internet of Thing (IoT), cloud security, smart card technology, CAPTCHA, digital signature and digital watermarking. Explains the latest functional encryption algorithms in a simple way with examples; Includes applications of functional encryption in information security, application security, and network security; Relevant to academics, research scholars, software developers, etc.
Introduction -- Foundations of Functional Encryption -- Mathematical Concepts and Properties -- Elliptic Curve Cryptography -- XTR Algorithm: Efficient and Compact Subgroup Trace Representation -- HECC: Hyperelliptic Curve Cryptography -- Pairing-Based Cryptography -- NTRU Algorithm: Nth Degree Truncated Polynomial Ring Units -- Cocks IBE Scheme -- Boneh-Franklin IBE -- Boneh-Boyen IBE -- Sakai-Kasahara IBE -- Hierarchical IBE -- Extensions of IBE and Related Primitives -- Attribute Based Encryption -- Digital Signatures -- Applications of Functional Encryption -- IRON: Functional Encryption Using Intel SGX -- Conclusion.
Electronic reproduction
Keywords: Data encryption (Computer science); Electronic books